ANALISIS FAKTOR PENDORONG PERDAGANGAN PEREMPUAN INDONESIA KE KAMBOJA DAN STRATEGI PEMULANGAN YANG EFEKTIF (STUDI KASUS TPPO DI KABUPATEN KARIMUN) - Efritadewi, Ayu; Sunarto, Dea Ayu Putri (Regalia: Jurnal Riset Gender dan Anak, 2025)
Human Trafficking Crimes (TPPO) are transnational crimes that violate human rights and have serious impacts on victims, especially women. This article aims to analyze the driving factors behind TPPO against Indonesian women to Cambodia, as well as to formulate effective strategies for the repatriation of victims. The study uses a normative legal approach by analyzing Law Number 21 of 2007 on the Eradication of TPPO and examining real cases involving a woman from Karimun Regency, Riau Islands. The findings indicate that the perpetrators' modus operandi has become increasingly sophisticated, utilizing social media to ensnare victims with promises of high-paying jobs. Vulnerability factors such as poverty, lack of information, and the weak socio-economic position of women are exploited by perpetrators through deception, forced labor, debt bondage, and communication cut-offs. This study highlights how the exploitation process is carried out systematically, from recruitment to being sent abroad, indicating the involvement of an organized human trafficking network. The strategy for repatriating victims of human trafficking cannot rely solely on logistical aspects but must include legal protection, psychological recovery, and social and economic reintegration. Challenges in repatriation include cross-border bureaucracy, victim identification, and the risk of revictimization if victims do not receive comprehensive support.This article recommends the need enhancing the capacity of families and communities in preventing human trafficking. This research is expected to contribute to the development of policies for the protection of female victims of human trafficking in Indonesia, particularly in the context of border areas and cross-border migration.